Tillväxt och potentiell sågtimmerkvalitet i gallringsmogna jämförelseplanteringar med Pinus contorta och P. sylvestris - Persson, Cecilia (SLU/Dept. of Forest Ecology and Management, 2008)
The Swedish Cellulosa Companiy, SCA, has today 280 000 ha planted with lodgepole pine (Pinus contorta var. latifolia) ("C") which is equivalent to 14 % of its total forest area. Exotic lodgepole pine has in previous experimental stands shown a superior growth than the native Scots pine (Pinus sylvestris L.) ("S").But also the comparison could be questioned because stand histories were was unknown and also differences in age between C and S existed. To establish a better comparison between the coniferous species initiated SCA in 1970 new experimental stands where C and S were planted under the same conditions. These experimental stands were measured 1979, 1984 and 1991 and the data were used for development of growth models. The purpose of this study was to follow up growth- and saw timber quality development in SCA´s experimental stands with C and S. On the basis of previous comparisons of the species the following hypothesis were formulated: • The total growth is up till now 50 % superior in C than in S • The dominant height in studied stands is developing according to height curves both for C and S • The "future stems" have almost the same saw timber quality in C and S Nine experimental stands from Åsarna in Jämtlad to Vilhelmina in Lapland (middle north Sweden) were visited in autumn 2007. In every experimental stand ten permanent plots were examined, five in C stands and five in S. On those plots all trees with dbh > 5 cm were callipered and height was measured on sample trees. About 20 "potential final cut trees" were appointed within a radius of 10 m and the criterion for those trees was that they visually showed on good saw timber quality. The total growth, including thinned trees for C was as a mean value 53 % higher than for S. The average growing stock was 179 m3sk/ha in C and 134 m3sk/ha in S. The development of C follows the yield models as predicted. Until 1991 C had a higher survival rate than S. Three C stands were tinned (9064, 9066 and 9072) in the beginning of 2000. Those stands had a higher ...